High-flow nasal cannula oxygen therapy was effective for dysphagia associated with respiratory muscle paralysis due to cervical spinal cord injury: A case report. Issue 32 (13th August 2021) - Watanabe, Yoshihiro; Tamura, Toshiaki; Imai, Ryota; Maruyama, Koki; Iizuka, Mayumi; Ohashi, Satomi; Yamaguchi, Seigo; Watanabe, Tatsunori
Abstract: Rationale: Respiratory muscle paralysis due to low cervical spinal cord injury (CSCI) can lead to dysphagia. Noninvasive positive airway pressure (PAP) therapy can effectively treat this type of dysphagia. High-flow nasal cannula (HFNC) oxygen therapy can generate a low level of positive airway pressure resembling PAP therapy, it may improve the dysphagia. Patient concerns: The patient was an 87-year-old man without preexisting dysphagia. He suffered a CSCI due to a dislocated C5/6 fracture, without brain injury, and underwent emergency surgery. Postoperatively (day 2), he complained of dysphagia, and the intervention was initiated. Diagnosis: Based on clinical findings, dysphagia in this case, may have arisen due to impaired coordination between breathing and swallowing, which typically occurs in patients with CSCI who have reduced forced vital capacity. Interventions: HFNC oxygen therapy was started immediately after the surgery, and swallowing rehabilitation was started on Day 2. Indirect therapy (without food) and direct therapy (with food) were applied in stages. HFNC oxygen therapy appeared to be effective because swallowing function temporarily decreased when the HFNC oxygen therapy was changed to nasal canula oxygen therapy. Outcomes: Swallowing function of the patient improved and he did not develop aspiration pneumonia. Lessons: HFNC oxygen therapy improved swallowing function in a patient with dysphagia associated with respiratory-muscle paralysis following a CSCI. It may have prolonged the apnea tolerance time during swallowing and may have improved the timing of swallowing. HFNC oxygen therapy can facilitate both indirect and direct early swallowing therapy to restore both swallowing and respiratory function.